Pengembangan Perangkat Pembelajaran Pada Materi Trigonometri Berbasis Tpack (Technology, Pedagogy, and Content Knowledge) Untuk Mengoptimalkan Kemampuan Pemecahan Masalah Matematis Peserta Didik - M. Eko Desryanto (Departement of Mathematics Education, 2023)
This type of research is research and development. The development model in this research is the 4-D model which consists of four development stages, namely define, design, develop, and disseminate. This research was designed using the 4-D model development design developed by Thiagarajan, Semmel, and Semmel. The 4-D model consists of 4 stages, namely define, design, develop, and disseminate. The basis for using this model in developing learning tools is because the 4-D model is a descriptive procedural model with systematic and more detailed stages. In the defining stage, the results of the analysis of learning needs on trigonometry material that can make students more active and optimize mathematical problem solving skills are obtained. The design stage consists of formulating assessment instruments, selecting media and formats and preparing initial product designs. In the develop stage, the product design is validated, revised, and tested. The developed product can be used by other schools as the disseminate stage.